2008
DOI: 10.1089/jmf.2007.553
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Byrsonima basiloba Extracts on the Mutagenicity of Certain Direct and Indirect-Acting Mutagens in Salmonella typhimurium Assays

Abstract: Byrsonima basiloba A. Juss. species is a native arboreal type from the Brazilian "cerrado" (tropical American savanna), and the local population uses it to treat diseases, such as diarrhea and gastric ulcer. It belongs to the Malpighiaceae family, and it is commonly known as "murici." Considering the popular use of B. basiloba derivatives and the lack of pharmacological potential studies regarding this vegetal species, the mutagenic and antimutagenic effect of methanol (MeOH) and chloroform extracts were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 41 publications
(43 reference statements)
2
43
0
Order By: Relevance
“…It is known that mutations are a major factor for the onset of cancer. However, chemoprevention, that is the prevention of cancer development by chemical substances that act as antimutagenic agents, with the capacity to interact with mutagenic compounds or their metabolites and reduce their effects, is one possible way to prevent cancer (Nogueira et al, 2006;Lira et al, 2008;Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that mutations are a major factor for the onset of cancer. However, chemoprevention, that is the prevention of cancer development by chemical substances that act as antimutagenic agents, with the capacity to interact with mutagenic compounds or their metabolites and reduce their effects, is one possible way to prevent cancer (Nogueira et al, 2006;Lira et al, 2008;Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical investigation of the leaves and stems afforded the flavonoids (+)-catechin, (-)-epicatechin, quercitrin and isoquercitrin, which are frequently found in Byrsonima species including B. basiloba, 6,7 B. bucidaefolia, 8 B. crassa, 9,10 B. crassifolia, [11][12][13][14] B. fagifolia, [15][16][17] B. intermedia, 18 B. microphylla, 19,20 and B. verbascifolia; 21,22 the investigation also afforded the tannins 3,5-di-O-galloylquinic acid, 5-O-galloylquinic acid, 5-O-(3-methylgalloyl)-quinic acid, 3,4,5-tri-O-galloylquinic acid and gallic acid, which have been previously described in B. crassa 9,10 and B. fagifolia. [15][16][17] Among the compounds isolated from the stems of B. coccolobifolia, (+)-syringaresinol and trigonostemone are new in the genus Byrsonima.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] The compounds most commonly isolated from this genus are flavonoids, terpenes, gallic acids and quinic acid derivatives. 1 Among the constituents, flavonoids (flavanones, bioflavonoids, flavonols and procyanidins), triterpenes (with oleanolic and ursolic skeletons) and modified triterpenoids (steroids) are commonly found in B. basiloba, 6,7 B. bucidaefolia, 8 B. crassa, 9,10 B. crassifolia, [11][12][13][14] B. fagifolia, [15][16][17] B. intermedia, 18 B. microphylla, 19,20 and B. verbascifolia. 21,22 Previous studies on the leaves of B. coccolobifolia revealed the presence of flavonoids, gallic acid and xanthones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaves and trunk barks from various species the Byrsonima are popularly employed in folk medicine to treat fever, gastrointestinal dysfunction (diarrhea and gastric ulcer), asthma, skin infections, and snakebites (Lira et al 2008, Mendes et al 1999 PATRÍCIA A. RODRIGUES et al al. 1999, Martínez-Vázquez et al 1999, bioactivity studies have demonstrated the gastroprotective, healing and antidiarrheal activities of B. fagifolia , the antimutagenic activity of B. basiloba (Lira et al 2008), and the mutagenic and gastroprotective effects of Byrsonima crassa (Cardoso et al 2006, Sannomiya et al 2007.…”
Section: Introductionmentioning
confidence: 99%